2015
DOI: 10.1111/pbr.12288
|View full text |Cite
|
Sign up to set email alerts
|

Relative efficiency of maize and Imperata cylindrica for haploid induction in Triticum durum following chromosome elimination‐mediated approach of doubled haploid breeding

Abstract: Intergeneric hybridization in seven diverse durum wheat genotypes was carried out using two composite varieties of Himalayan maize, viz., Bajaura Makka and Early Composite, and a wild grass, Imperata cylindrica, as pollen sources. Observations related to various haploid induction parameters put forth I. cylindrica as significantly better pollen source for haploid induction in durum wheat over maize in terms of pseudoseed formation (46.93%), embryo formation (38.06%), haploid regeneration (40.42%) and haploid f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Earlier, 2,4-D in combination with different growth promoters like, dicamba (Ballesteros et al 2003;Garcia-llamas et al 2004), picloram (Puja et al 2011) and AgNO 3 (Almouslem et al 1998;Inagaki and Hash 1998;Sourour et al 2011) had been tested for efficient haploid induction in durum wheat × maize crosses. Likewise, Chaudhary et al (2015) and, Mahato and Chaudhary (2015) reported the significant role of 2,4-D in haploid production via I. cylindrica-mediated chromosome elimination approach. It is evident from the findings of present study that higher concentrations of 2,4-D (more than 200 ppm) alone is well efficient in producing greater number of haploid embryos.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Earlier, 2,4-D in combination with different growth promoters like, dicamba (Ballesteros et al 2003;Garcia-llamas et al 2004), picloram (Puja et al 2011) and AgNO 3 (Almouslem et al 1998;Inagaki and Hash 1998;Sourour et al 2011) had been tested for efficient haploid induction in durum wheat × maize crosses. Likewise, Chaudhary et al (2015) and, Mahato and Chaudhary (2015) reported the significant role of 2,4-D in haploid production via I. cylindrica-mediated chromosome elimination approach. It is evident from the findings of present study that higher concentrations of 2,4-D (more than 200 ppm) alone is well efficient in producing greater number of haploid embryos.…”
Section: Discussionmentioning
confidence: 94%
“…Chaudhary et al (2005) and, Pratap and Chaudhary (2012) reported that 2,4-D at concentrations 100 and 250 ppm played an important role in induction of polyhaploids in crosses of bread wheat and bread wheat-rye derivatives with I. cylindrica, respectively. Chaudhary et al (2015) and, Mahato and Chaudhary (2015) also highlighted that haploid induction in durum wheat × I. cylindrica is most responsive at 250 ppm 2,4-D concentration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the last few years, chromosome elimination approach has proved to be the efficient system of doubled haploidy breeding as compared to other biotechnological tools like androgenesis mediated approach (Chu et al 1973;Ouyang et al 1973;Wang et al 1973). Chromosome elimination-mediated doubled haploidy breeding includes the various approaches viz., bulbosum technique (Barclay 1975), wheat × maize system Bennett 1987, 1988) and the recently discovered wheat × Imperata cylindrica system which has emerged as the best choice for haploid induction in wheat (Chaudhary et al 2005(Chaudhary et al , 2013a(Chaudhary et al , 2013bChaudhary 2008Chaudhary , 2009Chaudhary , 2010aChaudhary , 2010bKaila et al 2012) as well as in durum wheat (Mahato and Chaudhary 2015). Despite immense importance and advantages of doubled haploidy (DH) breeding, its extensive adoption in crop improvement programmes is lacking because of low frequency of production of doubled haploids due to high mortality rate of regenerated haploid plants after colchicine treatment.…”
Section: Introductionmentioning
confidence: 99%